Laser-triggered intelligent drug delivery and anti-cancer photodynamic therapy using platelets as the vehicle. (31st December 2023) - Li, Qi-Rui; Xu, Hua-Zhen; Xiao, Rong-Cheng; Liu, Bin; Ma, Tian-Qi; Yu, Ting-Ting; Li, Liu-Gen; Wang, Mei-Fang; Zhao, Li; Chen, Xiao; Li, Tong-Fei
Abstract: In our previous study, target drug delivery and treatment of malignant tumors have been achieved by using platelets as carriers loading nano-chemotherapeutic agents (ND-DOX). However, drug release from ND-DOX-loaded platelets is dependent on negative platelet activation by tumor cells, whose activation is not significant enough for the resulting drug release to take an effective anti-tumor effect. Exploring strategies to proactively manipulate the controlled release of drug-laden platelets is imperative. The present study innovatively revealed that photodynamic action can activate platelets in a spatiotemporally controlled manner. Consequently, based on the previous study, platelets were used to load iron oxide-polyglycerol-doxorubicin-chlorin e6 composites (IO-PG-DOX-Ce6), wherein the laser-triggered drug release ability and anti-tumor capability were demonstrated. The findings suggested that IO-PG-DOX-Ce6 could be stably loaded by platelets in high volume without any decrease in viability. Importantly and interestingly, drug-loaded platelets were significantly activated by laser irradiation, characterized by intracellular ROS accumulation and up-regulation of CD62p. Additionally, scanning electron microscopy (SEM) and hydrated particle size results also showed a significant aggregation response of laser irradiated-drug-loaded platelets. Further transmission electron microscopy (TEM) measurements indicated that the activated platelets released extracellularly their cargo drug after laser exposure, which could be taken up by co-cultured tumor cells. Finally, the co-culture model of drug-loaded platelets and tumor cells proved that laser-triggered delivery system of platelets could effectively damage the DNA and promote apoptosis of tumor cells. Overall, the present study discovers a drug-loaded platelets delivery using photodynamic effect, enabling laser-controlled intelligent drug delivery and anti-tumor therapy, which provides a novel and feasible approach for clinical application of cytopharmaceuticals. Graphic Abstract: uf0001 Plain Language Summaries: What is the context? 1. Platelets were applied to load IO-PG-DOX-Ce6, wherein the laser-triggered drug release and anti-tumor effect were investigated in vitro. 2. The findings indicated that IO-PG-DOX-Ce6 could be stably loaded by platelets in high volume without any decrease in viability, which may attribute to the activation of autophagy in platelets. 3. IO-PG-DOX-Ce6-loaded platelets could be significantly activated by laser irradiation (690 nm). 4. Activated platelets released extracellularly their cargo drug after laser exposure, which could be taken up by co-cultured tumor cells 5. The co-culture model of drug-loaded platelets and tumor cells proved that the laser-triggered delivery system of platelets could effectively damage the DNA and promote apoptosis of tumor cells. What is new? 1. Platelets could be utilized as the vehicle to load photosensitizer-loaded-nano-drug. 2. Photodynamic action can activate platelets in a spatiotemporally controlled manner, which could be a tool to regulate the activation of platelets. 3. The laser-triggered activation of drug-loaded platelets allows for target release of cargo. 4. The limitation of the current research is that only in vitro experiments were carried out to demonstrate our conclusions. What is impact? The present work provides a novel and feasible approach for the clinical application of cytopharmaceuticals.